2020
DOI: 10.1158/0008-5472.can-20-0521
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic Analysis of Subtype Evolution and Heterogeneity in High-Grade Serous Ovarian Carcinoma

Abstract: ◥Multiple studies have identified transcriptome subtypes of highgrade serous ovarian carcinoma (HGSOC), but their interpretation and translation are complicated by tumor evolution and polyclonality accompanied by extensive accumulation of somatic aberrations, varying cell type admixtures, and different tissues of origin. In this study, we examined the chronology of HGSOC subtype evolution in the context of these factors using a novel integrative analysis of absolute copy-number analysis and gene expression in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 53 publications
6
73
0
Order By: Relevance
“…spatial heterogeneity). Again, differences in the level of aneuploidy were expected as tumours exhibiting CIN are expected to produce heterogeneous populations of cells and our data support those of previous studies investigating the prevalence of genome instability within HGSOC [29,[37][38][39][40]. For example, Kim et al [38] and Schwarz et al [40] constructed evolutionary trees to describe the spatial heterogeneity identified in solid and ascites HGSOC samples.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…spatial heterogeneity). Again, differences in the level of aneuploidy were expected as tumours exhibiting CIN are expected to produce heterogeneous populations of cells and our data support those of previous studies investigating the prevalence of genome instability within HGSOC [29,[37][38][39][40]. For example, Kim et al [38] and Schwarz et al [40] constructed evolutionary trees to describe the spatial heterogeneity identified in solid and ascites HGSOC samples.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, by examining serial ascites samples, we determined that CIN is dynamic throughout the treatment period, and that higher levels of CIN are observed in chemoresistant disease relative to chemosensitive disease. Collectively, these temporal dynamics indicate that the level of CIN may reflect changes in the underlying biology associated with an individual's disease or reflect selection of chemotherapy-resistant cells produced in response to treatment, which is consistent with previous work proposing spatial changes in tumour phenotypes over time [29]. Perhaps most surprising, was the pervasive nature and extent of CIN within .…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study demonstrate greater interpatient differences than intrapatient differences and confirm the acknowledged tumor heterogeneity, as each patient sample displayed a unique combination of tumor, immune, and stromal cells, regardless of the method used for tumor dissociation. Several authors have illustrated the challenges of developing reliable diagnostic and therapy-related methods that can be applied to heterogeneous cancer tissues [13,[47][48][49]. The polyclonality and heterogeneity of HGSOC tumors, which has been established through single-cell experiments [13,[47][48][49], indicate a need for better profiling tools.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have illustrated the challenges of developing reliable diagnostic and therapy-related methods that can be applied to heterogeneous cancer tissues [13,[47][48][49]. The polyclonality and heterogeneity of HGSOC tumors, which has been established through single-cell experiments [13,[47][48][49], indicate a need for better profiling tools. Application of CyTOF in studies of HGSOC to detect cellular patterns rather than single biomarkers, potentially in combination with genetic biomarkers and preclinical modeling systems may provide breakthroughs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this premise, investigators have identified rare plastic pre-adapted cell subpopulations in luminal breast tumors which showed resistance to acute endocrine treatment [ 221 ]. Similarly, studies by Izar et al and Geistlinger et al used scRNA-seq based analyses to link the transcriptomic-based subtype classification of HGSOC to tumor cell type composition rather than intrinsic difference in gene expression patterns present in tumor epithelial cells further highlighting the importance of considering specific subpopulations of cells and the impact of signaling from the microenvironment on tumor characteristics [ 117 , 222 ]. More complex analyses integrating single-cell RNA-seq coupled with cell lineage tracing has been used to detail tumor cell subpopulations that contribute to various aspects of tumor evolution, including identifying pre-EMT (Epithelial to Mesenchymal Transition) cells that are essential for metastasis initiation [ 223 ].…”
Section: Advances In Genomic Analyses Of Breast and Ovarian Cancermentioning
confidence: 99%